We act as early as possible and prescribe for as long as possible! Individualised approach to statin therapy - M. V. Chirkova (Лечащий Врач)
Background. On 26-28 September, the Russian National Congress of Cardiologists 2024 was held in St. Petersburg. The event was accompanied by a satellite symposium supported by RECORDATI dedicated to practical aspects of personalised therapy. The focus was on modern approaches to the prevention of atherosclerotic cardiovascular diseases, the possibility of taking into account individual risk factors in comorbid patients and the safest options of drug therapy.Conclusion. Modern prophylactic and therapeutic measures, improvement of patients’ and doctor’ knowledge about statins therapy allow using them effectively and safely both in primary and secondary prevention of cardiovascular complications in all groups of patients.